The association of household Crowding and Tuberculosis incidence among Women of Varanasi City: A study in Medical Geography - Anupriya; Srivastava, G.N.; Mishra, Anand Prasad (National Geographical Journal of India, 2022)
Tuberculosis which was formerly called as a disease of poor is strongly associated with poverty and low socio-economic status. Overcrowding being an indicator of low socio-economic status also plays an important role in the tuberculosis incidence and transmission. Globally a number of researchers had tried to examine the impact of crowding on Tuberculosis incidence and its transmission, but due to over- reliance on ecological factors and in -consistent findings led to ignorance of this important risk factor. Keeping this in mind this research work tries to analyze the effects of overcrowding on Tuberculosis incidence among the women of the present study area. The result clearly shows that there is positive association between the incidence rate of tuberculosis and over-crowding .Thus Tuberculosis control programme should focus on making strategies for controlling over-crowding especially in the high incidence areas like religious city of Varanasi